Characterization of diatomite by X-Ray diffraction - Vargas-Infante, Carlos E.; Jiménez-Sánchez, Gabriela; Naranjo-Mechán, Wilson Enairo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
An X-Ray diffraction technique to was used to a detail detail characterization of the clay minerals in a diatomite deposit, which has not been studied nor explored, in order to determine its mining and industrial potential, located in the Tunja_Chivatá (Boyacá) pilot area.